Malonic acid: A potential reagent in decontamination processes for Ni-rich alloy surfaces - García, D. (2011)
The ability of malonic acid as a dissolution agent toward synthetic Ni ferrite and Alloy 600 and 800 corrosion products was explored. Its performance in the dissolution kinetics of Ni ferrite powders was compared with the one of oxalic acid. Kinetic parameters were obtained and the dependency on external Fe(II) was modelled. Oxidized samples used in descaling tests were prepared by exposure of coupons of both alloys to lithiated aqueous solutions, under hydrothermal conditions and hydrogen overpressure, simulating PHWR conditions. Oxide layer morphology, the influence of exposure time to corrosive medium and LiOH concentration on its thickness were characterized. Descaling tests consisting on a two-stage method (a first oxidizing step with alkaline permanganate followed by a reducing step with oxalic or malonic acid were carried out). Results were compared to those obtained with a well known chemical cleaning formulation (APAC: Alkaline Permanganate Ammonium Citrate) used in decontamination of several reactors and loops and the competitiveness of malonic acid was demonstrated.